Clinicopathological Characteristics of HPV-Related and HPV-Independent Cervical Cancer: Literature Review - Rahman, Hasmina; Nulanda, Mona; Sakti, Dachlia Sri (Journal of Asian-african Focus in Health, 2026)
Cervical cancer is one of the leading malignancies in women, and most cases are associated with high-risk Human Papillomavirus (HPV) infection, particularly HPV-16 and HPV-18. However, advances in classification and molecular pathology indicate that there is a group of cervical cancers that develop without HPV involvement, namely HPV-independent cervical cancer. This literature review aims to analyze the differences in clinicopathological characteristics of HPV-related and HPV-independent cervical cancer. This study uses a narrative literature review method by examining scientific articles obtained from Google Scholar, PubMed, ScienceDirect, Semantic Scholar, and SpringerLink in the publication period 2016–2026. The analyzed literature discusses clinical, histopathological, and molecular characteristics, prognosis, and therapeutic implications based on HPV status. The results of the study indicate that HPV-related cervical cancer generally occurs at a younger age, is dominated by squamous cell carcinoma, shows strong p16 expression, and has a better therapeutic response and prognosis. In contrast, HPV-independent cervical cancer is more common in older patients, is often diagnosed at an advanced stage, has histopathological subtypes such as gastric-type adenocarcinoma, clear cell carcinoma, and mesonephric carcinoma, and is associated with mutations in genes such as TP53, KRAS, PIK3CA, and PTEN. This group also exhibits higher tumor aggressiveness, more frequent lymphovascular invasion, a greater risk of recurrence, and a poorer prognosis. Therefore, HPV status plays a crucial role in determining the clinicopathological characteristics, prognosis, and therapeutic strategies of cervical cancer. Immunohistochemistry-based diagnostic approaches, molecular testing, and more individualized therapies are needed to improve diagnostic accuracy and patient outcomes.